Correlation of Ship Sanitation with Cockroach Density on Motor Vessel Docked in Port of Tanjung Perak Surabaya - Aqso Ampri Harahap (JURNAL KESEHATAN LINGKUNGAN, 2016)
Abstract: Based on data from Port Health Offi ce Class I Surabaya in 2012, 42 (1.66%) of 2.521 ship that were inspected was found vectors. Sanitation assessment data were found cockroach in July 2015, 9 (4.20%) of 214 ships, in August 15 (8.02%) of 187 ships, and in September 16 (8.88%) of 180 ships. Meanwhile Kepmenkes 431/2007 states that all water transportation have to be clean from vector and rodent. The objective of this study was to analyze correlation between ship sanitation and cockroach density. The design of this study was cross sectional. Samples was 30 ship that were docked at Port of Tanjung Perak Surabaya in October 2015. Sampling method was using accidental sampling. Data were obtained by questionnaire and observation Data were analyzed with Spearman correlation test. The result showed that 40.00% had high risk of health disorder and 91.67% of 40.00% was found high cockroach density There was a signifi cant correlation between ships sanitation and cockroach density. Not only all bins were not equipped with lid and water resistant materials but also poor personal hygiene of food handlers. It can be concluded that there was a correlation between ship sanitation and cockroach density. It is suggested to improve and maintain ship sanitation by equipping all of bins with lid and water resistant material and by increasing the personal hygiene of food handlers.Keywords: vessel sanitation, cockroach density, motor vessel